Pengaruh Aksesibilitas Bahan Pangan Terhadap Praktik Pemilihan Makanan Keluarga Selama Masa Pandemi: Pengaruh Aksesibilitas Bahan Pangan terhadap Praktik Pemilihan Makanan Keluarga di Kota Semarang selama Masa Pandemi - Kholidah, Laili Nur; Pangestuti, Dina Rahayuning; Lisnawati, Naintina; Asna, Alfi Fairuz (Universitas Airlangga, 2023)
Background: The COVID-19 pandemic has changed behavior and community's economic activities in Indonesia, resulting in a decrease in family food security. Good family food security is indicated by adequate food availability both in quantity and quality. Food resources should be safe, diverse, nutritious, evenly distributed, and accessible. Objectives: This study aims to analyze the effect of accessibility to family groceries on family diet practices in Semarang City during the COVID-19 pandemic. Methods: This cross-sectional study was conducted online in Semarang City in 2022. A total of 108 mothers of elementary school students were recruited using a purposive sampling technique. Data on general characteristics were obtained from an online questionnaire, while data on distance, affordability, sources of health information, and diet practices were obtained using a questionnaire which was then scored. The statistical analysis was conducted using the Chi-Square test with a significance level of 0.05. Results: The age of the mothers ranged from 36-45 years (64.8%); most of the mothers had a bachelor's degree (93.5%); the mothers worked (50.9%); the family income level was above Rp 2,800,000 (89.8%). Accessibility to information sources was limited in most cases (57.4%); the mothers' purchasing accessibility was high (63.9%); and they mostly could access food sources (71.3%). Most of the mothers had good diet practices (66.7%). Variables that showed a significant relationship with diet practices were accessibility to foodstuff (p = 0.001). Other variables that contributed to diet practices were the mothers' education (p = 0.040), occupation (p = 0.002), and family income (p = 0.006). Conclusions: There was a relationship between accessibility to food and diet practices.